Cold stress induces malformed tomato fruits by breaking the feedback loops of stem cell regulation in floral meristem. Issue 6 (20th January 2023) - Wu, Junqing; Sun, Wenru; Sun, Chao; Xu, Chunmiao; Li, Shuang; Li, Pengxue; Xu, Huimin; Zhu, Danyang; Li, Meng; Yang, Liling; Wei, Jinbo; Hanzawa, Aya; et al.
Summary: Fruit malformation is a major constrain in fruit production worldwide resulting in substantial economic losses. The farmers for decades noticed that the chilling temperature before blooming often caused malformed fruits. However, the molecular mechanism underlying this phenomenon is unclear. Here we examined the fruit development in response to cold stress in tomato, and demonstrated that short‐term cold stress increased the callose accumulation in both shoot apical and floral meristems, resulting in the symplastic isolation and altered intercellular movement of WUS. In contrast to the rapidly restored SlWUS transcription during the recovery from cold stress, the callose removal was delayed due to obstructed plasmodesmata. The delayed reinstatement of cell‐to‐cell transport of SlWUS prevented the activation of SlCLV3 and TAG1, causing the interrupted feedback inhibition of SlWUS expression, leading to the expanded stem cell population and malformed fruits. We further showed that the callose dynamics in response to short‐term cold stress presumably exploits the mechanism of bud dormancy during the seasonal growth, involving two antagonistic hormones, abscisic acid and gibberellin. Our results provide a novel insight into the cold stress regulated malformation of fruit.